2010
DOI: 10.4088/pcc.09m00873bro
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Treatment-Resistant Insomnia Taking Nightly Prescription Medications for Sleep

Abstract: In this treatment-seeking sample of patients regularly taking sleep medications, residual insomnia was widespread, and patients with psychiatric insomnia may have perceived their condition as more problematic than a control group of insomnia patients without mental health complaints. Both groups exhibited high rates of objectively diagnosed obstructive sleep apnea, a medical condition associated with pervasive sleep fragmentation. These findings support FDA and AASM guidelines to reassess chronic insomnia pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…11,14,29 In comparison to some studies conducted in non-veteran populations that employed a lower AHI threshold (AHI ≥ 5), our study's prevalence rate is slightly lower. 12,30,31 As described in our methods section, we chose a conservative AHI threshold of ≥ 15; our prevalence rate would have been much higher if we had selected an AHI ≥ 5. Compared to two other studies in non-veteran populations that employed the same AHI threshold used in our study, 11,14 we found a higher prevalence rate among older veterans.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,29 In comparison to some studies conducted in non-veteran populations that employed a lower AHI threshold (AHI ≥ 5), our study's prevalence rate is slightly lower. 12,30,31 As described in our methods section, we chose a conservative AHI threshold of ≥ 15; our prevalence rate would have been much higher if we had selected an AHI ≥ 5. Compared to two other studies in non-veteran populations that employed the same AHI threshold used in our study, 11,14 we found a higher prevalence rate among older veterans.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Given this evidence of long-term hypnotic use in insomnia, it is also of interest to assess long-term gender differences in the efficacy and safety of zolpidem. Controlled studies using polysomnography (PSG) to evaluate hypnotic efficacy for 6 months and beyond have shown continued efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In the only prior study of patients whose insomnia was resistant to treatment with prescription sleep-aids including BzRAs, levels of comorbid psychopathology were high. 6 However, this study lacked a comparator group of treatment responders, rendering it difficult to implicate comorbid psychopathology in treatmentresistance. Another report presented post hoc analyses of BzRA treatment from 5 different efficacy trials, including patients with "primary" insomnia and those with insomnia comorbid with depression, GAD, menopause, and arthritis.…”
Section: 38mentioning
confidence: 99%
“…[3][4][5] As such, efficacy in a controlled trial may not translate to effectiveness in clinical practice. A recent report 6 identified a series of sleep clinic patients with persistent insomnia symptoms despite chronic nightly use of prescription sleep-aids, of which BzRAs were the most commonly used and accounted for two-thirds of all sleep-aids. However, as only nonremitters were included in this study, rates of remission (and nonremission) from insomnia disorder among BzRA users in clinical settings is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation